Ábaco de pré dimensionamento de terças em perfil U formado a frio - Nascimento, Suelen Caroline do (2019)
Purlins are a constituent element of the roof of a building and have the function of supporting the tiles and transmitting the efforts acting on the plano f the roof to the trusses. The use of cold-fomed shapes as roofing purlins has been widely used in civil construction because it is a ligtweight and prefabricated material, making the execution of the work faster. Due to the wide variety of shapes available on the Market and the various possibilities of purlins loads, a support tool is needed to automate the design of this elemento. In this contexto, this work presentes a U-shapes design abacus with cold-formed edge stiffeners, using the Effective Sections Method, as laid down in NBR (ABNT,201). The final abacus uses the profiles standardized by NBR 6355 (ABNT,2012) and includes free spans purlins between 1,5 and 8 meters, spacing between purlins from 1,2 to 1,8 meters and wind pressure between 0,6 and 1,2 kN/m².